The Urgency of Psychology in Islamic Education: Building Cognitive, Affective, and Spiritual Balance in Education - Unang Sodikin; Samsuddin Samsuddin; Abdul Jabar Idharudin; Kamus Kamus; Balkis Nur Azizah; Ali Maulida; Mowafg Masuwd (Eduprof : Islamic Education Journal, 2026)
This article aims to explore the critical urgency of psychology within the Islamic paradigm and demonstrate how its systematic integration can strengthen the comprehensive and balanced nature of Islamic educational objectives. The study adopts a qualitative research design utilizing a literature review approach, with data analysis guided by the six-phase thematic analysis model to synthesize concepts from classical Islamic scholars and contemporary psychology. The findings confirm that psychology serves as a foundational element across all educational dimensions, including the formulation of goals, curriculum design, and teaching methodologies. Specifically, psychological insights are essential for understanding and nurturing fitrah (natural disposition), aligning educational goals with developmental stages, and promoting the spiritual purification process (tazkiyatun nafs). The discussion demonstrates that this integration results in a holistic development model that effectively balances the cognitive ('aql), affective (nafs), and spiritual (ruh) intelligence of students. Ultimately, the systematic incorporation of educational psychology ensures that Islamic schooling successfully equips learners with intellectual competence, strong moral character, and spiritual devotion, enabling them to contribute positively to society in accordance with Islamic principles.